Tingkat Kecemasan Peserta Didik dalam Mengikuti Pembelajaran PJOK Secara tatap Muka Terbatas Pada Masa Pandemi Covid-19 Di SMPN 6 Kota Bengkuu - Bader Adrean; Yarmani; Yahya Eko Nopiyanto (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the level of anxiety of students in participating in limited face-to-face PJOK learning during the Covid -19 pandemic at SMPN 6 Bengkulu City. In this study, researchers examined the anxiety of these students by using qualitative methods. The subjects in this study were all students at SMPN 6 Bengkulu City who were selected by academic achievement in the top 3 ranks in a class of 36 students. Instruments or tools in this study are observations, questionnaires, and interviews, this data processing technique uses data triangulation techniques consisting of the three instruments. Through these instruments and data processing techniques, the researchers also used the formula for determining the category of anxiety levels. The results of the observations in this study of 36 students who were observed based on the four indicators that became the reference were from these four indicators 13 students or 36% experienced anxiety and the results of the questionnaire On positive quest. Keywords: Anxiety, Covid -19 Pandemic, Physical Education Study Learning,